2016
DOI: 10.4171/pm/1983
|View full text |Cite
|
Sign up to set email alerts
|

The locus of Brill–Noether general graphs is not dense

Abstract: Abstract. We provide an example of a trivalent, 3-vertex connected graph G such that, for any choice of metric on G, the resulting metric graph is Brill-Noether special.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…If we fix a 2-coloring of the vertices of G, then the vertices of one color are a rank-determining set. This is the key observation in [Jen14], in which the second author shows that the Heawood graph admits a divisor of degree 7 and rank 2, regardless of the choice of edge lengths. The interest in this example arises because it shows that there is a non-empty open subset of the (highest-dimensional component of the) moduli space M …”
Section: Reduced Divisors and Dhar's Burning Algorithmmentioning
confidence: 82%
“…If we fix a 2-coloring of the vertices of G, then the vertices of one color are a rank-determining set. This is the key observation in [Jen14], in which the second author shows that the Heawood graph admits a divisor of degree 7 and rank 2, regardless of the choice of edge lengths. The interest in this example arises because it shows that there is a non-empty open subset of the (highest-dimensional component of the) moduli space M …”
Section: Reduced Divisors and Dhar's Burning Algorithmmentioning
confidence: 82%
“…The rest of this section is devoted to proving the following result: The graph G M from the corollary is known as the Heawood graph. A similar graph but with generic edge lengths was used by Jensen to show that the locus of Brill-Noether general graphs is not dense in the moduli space of tropical curves [8]. Let (L, H) be a linear series on a nodal curve X.…”
Section: Dependence Of the Algebraic Rank On The Ground Fieldmentioning
confidence: 99%
“…Remark 17. In recent work, Jensen [9] showed that the Haewood graph is a Brill-Noether special metric graph for arbitrary edge lengths, thus showing that the locus of Brill-Noether general metric graphs is not dense in the tropical moduli space. Figure 6.…”
Section: 3mentioning
confidence: 99%